EEG analysis of trial subjects with discirculatory encephalopathy by multidimensional scaling method of cognitive tests and leads - Anna I. Novikova; Kaleria A. Moroz; Elena A. Kizhevatova (Advanced Engineering Research)
Introduction. The EEG-data of patients with discirculatory encephalopathy and healthy subjects by the multidimensional scaling method are analyzed. The research subject is graphs of the vectors arrangement dynamics in the two-dimensional attribute space of EEG-data of healthy and patient subjects corresponding to each of the leads and cognitive tests. The aim was to test feasibility of the multidimensional scaling method in the EEG analysis for the classification of trial subjects for patients and healthy persons. The study objectives are the following: EEG taking in trial subjects with simultaneous testing for cognitive deteriorations; multidimensional scaling of correlation matrices in the STATISTICA system, and visual analysis of the obtained graphs. Materials and Methods. Capabilities of the multivariable technique of statistical analysis of test data - multidimensional scaling - the STATISTICA software package - are investigated. The processed data are obtained as a result of recording EEG of healthy subjects and patients with discirculatory encephalopathy using “Encephalan-131-03” electroencephalograph from 16 unipolar leads. The EEG is taken by simultaneous testing of the trial subjects by cognitive tests. Research Results. Visual analysis of the multidimensional scaling diagrams of healthy subjects has shown that the distribution of the pairwise coordinates corresponding to the tests (leads), for each of the leads (test) is characterized, generally, by a close location of the coordinates relative to each other, and in some cases - by coincidence. In patients with discirculatory encephalopathy, two-dimensional planes of the multivariate scaling are characterized by a more chaotic distribution of the spatial coordinates of each of the leads or test. Discussion and Conclusions. The efficiency effect of the multidimensional scaling as a classifier of trial subjects’ EEG is confirmed. The possibility of using the multidimensional scaling as an additional method in the diagnosis of discirculatory encephalopathy is proposed.